An?lise de desempenho de algoritmos de decodifica??o para c?digos LDPC regulares - Magalh?es, Fernanda Pinto (2007)
The purpose of this master degree thesis is to analyze the decoding performance of decoding algorithm for low density parity check codes, the LDPC codes. The main characteristics of the encoding scheme and its construction are presented on this work, as well as, three decoding algorithms for the proposed LDPC encoding technique. A simulator was also developed in Mathlab/Simulink to conduct a performance analysis and comparison of the target decoding algorithm.